Botanical concrete. Experimentation on concrete substrates for vertical greening - Lucas Büscher; Roman Polster; Heike Klussmann (Agathón)
Botanical Concrete collaboratively investigates a fundamentally new approach to wall-based vertical greening systems, based on design thinking, materials research and phytotechnology, to functionalize concrete and allow the permanent establishment of cryptogams and tracheophytes on its surface, two species with different substrate demands requiring two different sets of parameters for functionalisation. Combining the results of research into cryptogams and tracheophytes produces a novel, resource-conserving approach to vertical greening, able to take advantage of the impermeable surfaces commonly found in built space to establish vegetation, improve local microclimates, increase urban biodiversity, and create new biotopes.